Escape from the great earthquake - Messner, Kate; McMorris, Kelley (New York : Scholastic Inc., 2017)
This time Ranger, the time-traveling Golden retriever, finds himself in San Francisco in the middle of the great 1906 earthquake, and his mission is obviously to get a young Chinese immigrant, Lily Chen, to safety, but as they make their way through the ruined and burning city Ranger finds that he must also accomplish something else--finding Lily, who was sold as a servant by her parents, a new family who will care for her.
Includes bibliographical references.
4.4.
3-6.
630L
Keywords: Golden retriever -- Juvenile fiction; San Francisco (Calif.) -- History -- Juvenile fiction; Golden retriever -- Fiction; Dogs -- Fiction; San Francisco Earthquake and Fire, Calif., 1906 -- Fiction; Chinese Americans -- Fiction; San Francisco (Calif.) -- History -- 20th century -- Fiction; Golden retrievers -- Fiction; Dogs -- Fiction; San Francisco Earthquake and Fire, Calif., 1906 -- Fiction; Chinese Americans -- Fiction; San Francisco (Calif.) -- History -- Fiction; Action and adventure fiction; Time-travel fiction